FEATURES OF THE BIOGEOMETRIC PROFILE OF YOUNG CHEERLEADERS WITH DIFFERENT POSTURE TYPES AS A PREREQUISITE FOR THE DEVELOPMENT OF PHYSICAL THERAPY PROGRAMS - Grygus, I. M.; Zeiser, T. V.; Kasianchuk, V. M. (Rehabilitation and Recreation, 2025)
Introduction. Previous observations show that the type of posture correlates with the state of the bio-geometric profile. However, there is no deep understanding of how different types of posture (normal, scoliotic, hunched back) affect the spatial organization of the body, and what specific changes occur in the biogeometric profile depending on the existing posture disorders. The solution to this problem will allow the development of scientifically based approaches to diagnostics, monitoring and correction of posture in young athletes, ensuring their optimal physical development and preventing possible injuries.The purpose of the study is to conduct a comparative analysis of the biogeometric profile of young cheerleaders with different types of posture to identify key deviations and prerequisites for their progression, which will allow the development of targeted physical therapy programs.Research methods: theoretical analysis of specialized literature; medical and biological research methods (photography), visual screening of posture, methods of mathematical statistics.Results. The study of quantitative characteristics of the biogeometric profile revealed significant differences between the groups of athletes with different types of posture. Athletes with normal posture haddominant high and medium scores, indicating optimal spatial organization of the body. The average value in the sagittal plane was 12.67 ± 1.63 points, in the frontal plane – 10.17 ± 1.60 points, and the total score was 22.83 ± 3.13. In contrast, girls with a hunched back showed a statistically significant decrease in all indicators: 9.50 ± 2.01 points in the sagittal plane, 8.10 ± 1.85 points in the frontal plane, and 17.60 ± 2.80 points for the total score. The lowest values were found in the group of female athletes with scoliotic posture, reflecting the most pronounced violations of the biogeometric profile: 9.00 ± 0.94 points in the sagittal plane, 7.30 ± 1.95 points in the frontal plane, and 16.30 ± 1.64 points for the total score.These results indicate a transition to a low level of the biogeometric profile, being on the border betweenlow and medium levels.Analysis of the frequency distribution of biogeometric profile assessments allowed us to identify riskzones for posture disorders in cheerleaders. These are the ranges of values that intersect between groups with normal posture and those with disorders. These zones indicate the potential presence of deviations even in girls whose posture is visually assessed as normal. Specifically, the threshold values that may indicate hidden disorders are: sagittal plane – 12 points, frontal plane – 10 points, total score – 20–22 points.Conclusions. Identification of the specified threshold values in young athletes should serve as a signalfor immediate in-depth diagnostics and immediate implementation of preventive corrective measures. Thisapproach will allow for timely detection and correction of initial deviations, effectively preventing theirprogression and ensuring harmonious physical development of cheerleader athletes. In view of this, timely physical therapy is critically important. Early intervention and corrective work using special exercises aimed at strengthening the muscle corset and restoring the biomechanics of movements will prevent the progression of latent deviations to the stage of clinically pronounced posture disorders.